EKSISTENSI DAN IMPLIKASI RECAAP TERHADAP PENGUATAN KEAMANAN MARITIM DI KAWASAN ASIA TENGGARA - Muhammad Alif Andyva , Agussalim Burhanuddin (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
ReCAAP was founded with an aim to fight against sea-piracy and armed robbery that affected Southeast Asia maritime security. In doing so, ReCAAP helped by providing important information, increasing coordination between focal points, and enhancing the members’ ability to adapt with piracy and armed robbery at sea. However, there were challenges for ReCAAP to ensure the maritime security, including law enforcement ability and measurement on suspected individuals. On the other hand, ReCAAP had political influences in terms of states relationship in the region, and strategically, empowering maritime security. This led to a more complex situation in order to achieve stability, particularly when there was a possible hinder of good relationship between neighboring states in the region.